(untitled) (Scientiae Studia, 2017)
In this article we read, with feminist lens, two historical infl uences of Latin American thinking on Social Technology. At fi rst, we look at the independence movement of India in the fi rst half of the twentieth century, which fostered a policy of dissemination of the Charkha, a kind of spinning wheel. Widespread in the period in which Gandhi led the movement, the wheel has become a symbol of the nationalist struggle, and is seen as an emblematic example of a socio-technical alternative. In a second step, we analyze the Appropriate Technology Movement, as a set of ideas and initiatives that popularize in the 1970s the dissemination of technologies supposedly appropriate to the reality of the impoverished regions of the “south”. In order to fi ll in the analytical gender gaps, we highlight the contributions of authors who unvail the androcentric character of such policies, and explain how inadequate technologies were produced because women’s work and community care needs in rural Africa and Asia were hidden. Finally, we weave connections between gender and the construction of socio-technical alternatives, and argue that it is in virtue of the invisibility of the feminized character of care, and of an uncritical incorporation of productivist logic that Social Technology embodies androcentrism